(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe some adverse reactions after Pfizer vaccine against COVID-19 at Hai Dương Medical Technical University in 2022. Research methods: Cross-sectional study describe some adverse reactions in individuals who received Pfizer COVID-19 vaccine. The research team distributed questionnaires to 582 officials, employees and students of Hai Duong Medical Technical University who had received the Pfizer COVID-19 vaccine and received all 4 doses. Research results: The among the total of 582 study participants, 79.1% were female; 33.5% were mainly aged 18-25; 16.7% had a history of allergies; 15.9% had a history of illness; 41.9% had pain at the injection site after the first injection; 36.1% had fever; 16.5% had headache, and 18.9% had muscle pain and fatigue. Conclusion: Some of the most common side effects after receiving the Pfizer COVID-19 vaccine are pain, heat, redness, itching, and swelling at the injection site. Other side effects include fatigue, headache, dizziness, muscle pain, joint pain, fatigue, sore throat, runny nose, cough, and fever.